Constructing scale for the arts of dealing with others and illustrated etiquette among kindergarten children (Journal of the College of Basic Education, 2024)
The current research aims Constructing scale for the arts of dealing with others and illustrated etiquette among kindergarten children. The research sample consisted of (200) male and female children aged (5-6) years in the (primary stage) from the (Jannat Al-Zahra) kindergarten affiliated with the Governorate Education Directorate. Al-Najaf Al-Ashraf, and to verify the objectives of the research, the two researchers built an illustrated scale for the arts of dealing with others (etiquette) for the kindergarten child, in which it relied on social learning theory. The scale for the arts of dealing with others included (50) items distributed over (10) arts, and was The psychometric properties of the scale were extracted, including validity and reliability. The data was analyzed and processed statistically using the Statistical Package for Psychological and Social Sciences (SPSS), and the two researchers concluded with a set of recommendations and proposals.